HAEMATOLOGICAL ALTERATIONS FOLLOWING VARIOUS THERAPIES IN SURT.I BUFFALOES WITH POSTPARTUM METRITIS - PATIL, R D; PATEL, J A; HADIYA, K K; DHAMl, A J (The Indian Journal of Animal Reproduction, 2023)
This study was carried out under field condition on 40 Surti buffaloes with postpartum metritis divided into five groups of eight animals each. The study included use of four treatment lines and one control group, viz., Group 1- Metronidazole (500 mg) 1/U for 5 days; Group II- Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) 1/U for 5 days; Group Ill- Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) 1/U for 5 days plus PGF2 , 25 mg i/m once on first day; Group IV- Ceftlofur (long acting)@ 6.6 mg/kg body weight subcutaneously once and Group V (control)- Normal saline 1/U for 5 days. The effects of these therapeutic regimes were evaluated by comparing the clinical and haematological alterations before and 6 days after treatment. The mean values of Hb, PCV and TEC after four treatments were significantly (P<0.05) higher than the corresponding pre-treatment values, however no significant differences were observed in pre- and post-treatment values of control group. Similarly, mean TLCs on day 6 post-treatment were significantly (P<0.01) lower trian the pre-treatment TLC vr.1lues in all four treatment groups. The mean neutrophil count was found to be significantly (P<0.01) decreased and the lymphocyte count increased in groups 11, Ill and IV on day 6 post-treatment, whereas in group l, both the values were found to vary significantly (P<0.05). No significant differences were observed in pre- and posttreatment values of monocytes and eosinophils in the treatment groups, and control group. The changes in haematological profile were related to the degree of improvement of the clinical conditions of the animals.